Management of locoregional recurrence after radical resection of a primary nonmetastatic retroperitoneal soft tissue sarcoma: The Gustave Roussy experience. Issue 8 (6th November 2018) - Honoré, Charles; Faron, Matthieu; Mir, Olivier; Haddag‐Miliani, Leila; Dumont, Sarah; Terrier, Philippe; LePéchoux, Cecile; Botticella, Angela; Adam, Julien; Le Cesne, Axel
Abstract : Background: Despite surgery, many patients experience locoregional recurrence (LR), the optimum treatment of which is still debated. Methods: All 297 consecutive patients operated for a nonmetastatic primary retroperitoneal soft tissue sarcoma (RPS) between 1994 and 2017 were retrospectively analyzed to report our experience in treating LR. Results: After a median follow‐up of 97 months, 55 patients (19%) developed LR. The first site of recurrence was locoregional in 100% with associated peritoneal metastases in 45% and distant metastases in 5%. After LR treatment, the 1‐, 3‐, and 5‐year overall survival (OS) rates were 71%, 46%, and 33%. Low tumor grade, disease‐free interval above 24 months, exclusive LR, and well‐differentiated liposarcoma were predictive of better OS. The treatment strategy (best supportive care, chemotherapy radiotherapy, and/or surgery) was not statistically significant. Fourteen patients underwent initial surveillance (strategic delay) for low‐grade LR and eventually required treatment in 86% after a median delay of 20 months during which no patient developed distant metastases. Conclusions: The management of LR in RPS is complex. An initial surveillance may not alter survival in asymptomatic low‐grade and slow‐growing LR. An LR decision scheme is proposed.